High-performance anti-aging PC / PBT alloy material and preparation method thereof
By using composite anti-hydrolyzers and tetrabromobenzene A polycarbonate in PC/PBT alloy materials, the problems of deterioration in mechanical properties and unstable fire resistance in high temperature and high humidity environments are solved, and the high-performance anti-aging effect is achieved.
Patent Information
- Application Number
- CN202411923708.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-29
AI Technical Summary
When used in high temperature and high humidity environments, the mechanical properties of existing flame retardant PC/PBT alloy materials become deteriorated and the fire resistance is unstable, so they cannot be used in industrial production for a long time.
Complex anti-hydrolyzer and tetrabromobenzene A polycarbonate are used as main flame retardants, combined with anti-drip synergist, compatible toughener and nucleating agent to form high-performance anti-aging PC/PBT alloy material.
The mechanical properties and fire resistance of PC/PBT alloy materials are significantly improved in high temperature and high humidity environments, ensuring the long-term stability and application value of the materials in harsh environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a high-performance anti-aging PC / PBT alloy material. Background Art
[0002] PC / PBT alloy is a thermoplastic alloy material with excellent comprehensiveness, good heat resistance and excellent chemical resistance. It is widely used in new energy batteries, automotive industrial parts, charging and replacement parts, and household appliances. With people's emphasis on safety, fire safety performance is given in applications. PC / PBT alloy materials not only need to have good mechanical and chemical resistance, but also good flame retardancy. In the current research on PC / PBT alloy materials, phosphorus flame retardants can be used as flame retardants for PC / PBT alloys. Phosphorus flame retardants are represented by phosphate esters. This type of flame retardant is an ester itself, and has a small molecular weight and is easily induced to hydrolyze by the environment. When it is added to PC / PBT as a flame retardant, it will accelerate the hydrolysis of PC / PBT. The inventor has done a test. After 168 hours of testing in a constant environment of high temperature 85℃ and high humidity 85℃, the PC / PBT alloy prepared by the flame retardant system completely loses the performance of plastic. For this reason, bromine is considered as the main flame retardant, and the anti-drip synergistic flame retardant is used. Its flame retardant effect and high temperature and high humidity stability are better than the phosphate system.
[0003] In recent years, new energy vehicles, new energy batteries, charging piles, and aerospace military materials have flourished, driving the rapid development of high-performance anti-aging PC / PBT alloy materials and related industries. The high temperature and high humidity resistant PC / PBT alloy material of the present invention can be applied to new energy batteries, charging guns, automobile industry and aerospace fields, with broad industrialization prospects and high economic value. Summary of the invention
[0004] The present invention aims to improve the existing flame-retardant PC / PBT alloy materials, which have defects such as poor mechanical properties and unstable fire resistance when used for a long time in a high-temperature and high-humidity environment, and prepare a PC / PBT alloy that can be used in a high-temperature and high-humidity environment. The PC / PBT alloy can meet the needs of automotive industry parts and new energy battery internal and external parts, and has great social application value.
[0005] The object of the present invention is to provide a high-performance anti-aging PC / PBT alloy material.
[0006] Another object of the present invention is to provide a method for preparing a high-performance anti-aging PC / PBT alloy material.
[0007] The technical solution adopted by the present invention is:
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A high-performance anti-aging PC / PBT alloy material comprises the following raw materials in parts by weight:
[0010]
[0011] The PC resin has a medium-low viscosity and a melt index of 6-10g / 10min.
[0012] The polybutylene terephthalate has a medium viscosity of 0.8-1.2.
[0013] The tetrabromobisphenol A polycarbonate has a bromine content of ≥52%.
[0014] The anti-drip synergist is a coated PTFE anti-drip agent.
[0015] The compatible toughening agent is EMA grafted GMA.
[0016] The compound anti-hydrolysis agent is a compound hydrolyzing agent composed of an antioxidant, a benzotriazole ultraviolet absorber, an ester exchange inhibitor, and a styrene-acrylonitrile-glycidyl acrylate copolymer in a certain ratio.
[0017] The lubricant is a silicone lubricant.
[0018] The nucleating agent is an optimized mixture of organic components and inorganic components.
[0019] The preparation method of the above-mentioned high-performance anti-aging PC / PBT alloy material comprises the following steps:
[0020] 1) Weigh various raw materials according to the formula;
[0021] 2) Dry PC, tetrabromobisphenol A polycarbonate, and PBT resin at 120° C. for 3-4 hours, and then mix them evenly with all other raw materials;
[0022] 3) The mixed raw materials are placed in the lower hopper of the extruder, and melt-extruded and granulated by a twin-screw extruder to obtain a high-performance anti-aging PC / PBT alloy material.
[0023] Compared with the prior art, the present invention has the following advantages and effects:
[0024] 1) The present invention creatively proposes a composite anti-hydrolysis agent. If the composite anti-hydrolysis agent is added in a certain proportion, it can overcome the problem that the ester group of PC / PBT polyester alloy is easily hydrolyzed under high temperature and high humidity, causing degradation and ester exchange, and ultimately leading to a significant decrease in the mechanical properties and fire resistance of the PC / PBT alloy material, making it impossible to use it for a long time in industrial production in harsh environments.
[0025] 2) The principle of the anti-hydrolysis agent of the present invention is as follows: 1. By adding EMA grafts, on the one hand, EMA is insensitive to water. By using the principle of molecular reaction, EMA can be added to the molecular structure of PC / PBT to isolate water molecules from reacting with PC / PBT. On the other hand, the GMA group in BF-7M itself has hydrolysis resistance, is not affected by the temperature and humidity, will not be hydrolyzed, and has a long-term toughening effect; 2. By using the characteristics of the highly active epoxy group of GMA in SAG008, the group that hydrolyzes under high temperature and humidity is captured to carry out chain termination reaction, inhibit hydrolysis, and protect the integrity of the molecular weight; 3. Ester exchange The role of the inhibitor is to inhibit the reaction between PBT and PC ester groups. At 85°C, the molecular chain of PBT breaks through the glass state. The addition of the ester exchange agent just inhibits the reaction between PC and PBT ester groups, thereby avoiding the hydrolysis reaction of the ester group; 4. Antioxidant 1076 is a good long-term aging agent, which mainly protects the molecular breakage and reaction at high temperature; 5. Benzotriazole mainly uses the characteristics of its own phenols that can form hydrogen bonds, which can absorb a large amount of energy, release heat, and then continue to form its own hydrogen bond cycle characteristics. It can well protect the stability of polyester molecules under high temperature and high humidity, thereby protecting the material and inhibiting the hydrolysis of the material. The above compound anti-hydrolysis agents must be added in a specific proportion and fixed amount to be effective.
[0026] 3) The present invention adopts tetrabromobisphenol A polycarbonate as the main flame retardant. On the one hand, the flame retardant has a large molecular weight, and its hydrolysis resistance and carbon formation performance are stronger than other bromine-based flame retardants such as brominated triazine, decabromodiphenylethane and brominated epoxy resin; on the other hand, the flame retardant has excellent compatibility with PC and PBT, and can withstand high-temperature processing at 300°C without being decomposed, making it the most suitable flame retardant for this system. DETAILED DESCRIPTION
[0027] 18-77 parts of polycarbonate (PC) resin, 10-55 parts of polybutylene terephthalate (PBT) resin, 5-20 parts of tetrabromobisphenol A polycarbonate, 0.2-0.5 parts of anti-drip synergist, 0.1-0.5 parts of nucleating agent, 1-7 parts of compatible toughening agent, 4-9 parts of compound anti-hydrolysis agent, and 0.5-1 parts of lubricant.
[0028] The melt index of the above PC resin is about 6-10g / 10min.
[0029] The polybutylene terephthalate described above has a medium viscosity, and the viscosity is 0.8-1.2.
[0030] The anti-drip synergist is a coated PTFE anti-drip agent.
[0031] The tetrabromobisphenol A polycarbonate described above has a bromine content of ≥52%.
[0032] The compatible toughening agent mentioned above is EMA grafted GMA.
[0033] The above-mentioned composite anti-hydrolysis agent is a composite hydrolysis agent composed of an antioxidant, a benzotriazole ultraviolet absorber, an ester exchange inhibitor, and a styrene-acrylonitrile-glycidyl acrylate copolymer in a certain ratio.
[0034] The nucleating agent mentioned above is an optimized mixture of organic and inorganic components.
[0035] The lubricant mentioned above is silicone powder.
[0036] A high-performance anti-aging PC / PBT alloy material and a preparation method thereof, comprising the following steps:
[0037] 1) Weigh various raw materials according to the above-mentioned formula,
[0038] 2) Drying PC, tetrabromobisphenol A polycarbonate, and PBT resin at 120° C. for 3-4 hours;
[0039] 3) Weigh PC resin, PBT resin, tetrabromobisphenol A polycarbonate, PTFE anti-dripping agent, compound anti-hydrolysis agent, nucleating agent and lubricant according to mass ratio and mix them in a high-speed mixer for 3 minutes; add the mixed materials into the hopper of a twin-screw extruder for mixing, extrusion and granulation. Then, a high temperature and high humidity resistant PC / PBT alloy can be obtained.
[0040] Preferably, the process parameters of the twin-screw extruder melt extrusion granulation are: zone 1 temperature 230-240°C, zone 2 temperature 245-255°C, zone 3 temperature 245-255°C, zone 4 temperature 245-255°C, zone 5 temperature 240-245°C, zone 6 temperature 235-240°C, zone 7 temperature 230-230°C, zone 8 temperature 225-230°C, zone 9 temperature 225-230°C, and die head temperature 240-245°C. The main engine speed is 300-350r / min, and the feeding speed is 200-250r / min.
[0041] The present invention is further described below with reference to specific embodiments, but is not limited thereto.
[0042] The components used in all the following examples are as follows:
[0043] Component 1: PC medium-high viscosity resin, the optional melt index is 6-10g / 10min, the preferred melt index is 7g / 10min, and Wanhua PCA1077 is selected;
[0044] Component 2 is PBT resin, with a viscosity of 0.8-1.2, preferably Xinjiang Tunhe PBT TH6100, with a viscosity of 1.0;
[0045] Component three is tetrabromobisphenol A polycarbonate, with a bromine content of ≥52, and LANXESS BC58 is selected;
[0046] Component 4 is PTFE anti-dripping agent, which requires more than 98% of particle size <10 mesh, PTFE content >45%, and Entropy SN3300B7 is selected;
[0047] Component five is a compatible toughening agent, which uses Japan's Sumitomo BF-7M;
[0048] Component six is a compound anti-hydrolysis agent, which includes: Japan Aidico ester exchange inhibitor AX-71, Jiayirong styrene-acrylonitrile-glycidyl acrylate copolymer SAG-008, BASF antioxidant 1076, BASF benzotriazole ultraviolet absorber UV326, which are compounded in proportion;
[0049] Component seven is a nucleating agent, and Brueggemann P252 is selected;
[0050] Component eight is a lubricant, silicone powder, Dow Corning 4-7084.
[0051] Example 1 A high-performance anti-aging PC / PBT alloy material and its preparation method
[0052] 1) Weigh the following raw materials in parts by mass: 77.2 parts of PC resin, 10 parts of PBT resin, 5 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 3 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, and 0.3 parts of lubricant 4-7081.
[0053] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0054] SAG008:AX-71:UV326:1076=3:0.5:1:0.5;
[0055] 3) Weigh 76.7 parts of PC resin, 10 parts of PBT resin, 5 parts of tetrabromobisphenol A polycarbonate, 0.3 parts of SN3300B7 anti-drip synergist, 3 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, and 0.3 parts of lubricant 4-7081 according to the mass ratio, and mix them in a high-speed mixer for 3 minutes; add the mixed material into the hopper of the twin-screw extruder, add carbon fiber through the side feeding system, mix, extrude, and granulate. Then, a high temperature and high humidity resistant PC / PBT alloy can be obtained.
[0056] Preferably, the process parameters of the twin-screw extruder melt extrusion granulation are: zone 1 temperature 230-240°C, zone 2 temperature 245-255°C, zone 3 temperature 245-255°C, zone 4 temperature 245-255°C, zone 5 temperature 240-245°C, zone 6 temperature 235-240°C, zone 7 temperature 230-230°C, zone 8 temperature 225-230°C, zone 9 temperature 225-230°C, and die head temperature 240-245°C. The main engine speed is 300-350r / min, and the feeding speed is 200-250r / min.
[0057] Example 2 A high-performance anti-aging PC / PBT alloy material and its preparation method
[0058] The preparation method of Example 2 is the same as that of Example 1, except that the mass fractions of the raw materials used are different.
[0059] The weight fractions of each raw material in this embodiment are as follows:
[0060] 1) Weigh the following raw materials in parts by mass: 55.6 parts of PC resin, 25 parts of PBT resin, 10 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 4 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, 0.1 parts of nucleating agent P252, and 0.3 parts of lubricant 4-7081.
[0061] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0062] SAG008:AX-71:UV326:1076=3:0.5:1:0.5;
[0063] Example 3 A high performance anti-aging PC / PBT alloy material and its preparation method
[0064] The preparation method of Example 3 is the same as that of Example 1, except that the mass fractions of the raw materials used are different.
[0065] The weight fractions of each raw material in this embodiment are as follows:
[0066] 1) Weigh the following raw materials in parts by mass: 37 parts of PC resin, 37.5 parts of PBT resin, 15 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 5 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, 0.2 parts of nucleating agent P252, and 0.3 parts of lubricant 4-7081.
[0067] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0068] SAG008:AX-71:UV326:1076=3:0.5:1:0.5;
[0069] Example 4 A high performance anti-aging PC / PBT alloy material and its preparation method
[0070] The preparation method of Example 4 is the same as that of Example 1, except that the mass fractions of the raw materials used are different.
[0071] The weight fractions of each raw material in this embodiment are as follows:
[0072] 1) Weigh the following raw materials in parts by mass: 19.5 parts of PC resin, 50 parts of PBT resin, 20 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 5 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, 0.2 parts of nucleating agent P252, and 0.3 parts of lubricant 4-7081.
[0073] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0074] SAG008:AX-71:UV326:1076=3:0.5:1:0.5;
[0075] Example 5 A high performance anti-aging PC / PBT alloy material and its preparation method
[0076] The preparation method of Example 5 is the same as that of Example 1, except that the mass fractions of the raw materials used are different.
[0077] The weight fractions of each raw material in this embodiment are as follows:
[0078] 1) Weigh the following raw materials in parts by mass: 18 parts of PC resin, 50 parts of PBT resin, 20 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 5 parts of compatible toughening agent BF-7M, 6.5 parts of compound anti-hydrolysis agent, 0.2 parts of nucleating agent P252, and 0.3 parts of lubricant 4-7081.
[0079] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0080] SAG008:AX-71:UV326:1076=4:0.8:1:0.7;
[0081] Example 6 A high performance anti-aging PC / PBT alloy material and its preparation method
[0082] The preparation method of Example 6 is the same as that of Example 1, except that the mass fractions of the raw materials used are different.
[0083] The weight fractions of each raw material in this embodiment are as follows:
[0084] 1) Weigh the following raw materials in parts by mass: 36 parts of PC resin, 35 parts of PBT resin, 15 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 5 parts of compatible toughening agent BF-7M, 8.5 parts of compound anti-hydrolysis agent, 0.2 parts of nucleating agent P252, and 0.3 parts of lubricant 4-7081.
[0085] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0086] SAG008:AX-71:UV326:1076=4:0.8:1:0.7;
[0087] Example 7 A high performance anti-aging PC / PBT alloy material and its preparation method
[0088] The preparation method of Example 7 is the same as that of Example 1, but the main materials are selected from different manufacturers with the same MI and viscosity, and other conditions are the same.
[0089] 1) Weigh the following raw materials in parts by mass: 77.2 parts of PC resin, 10 parts of PBT resin, 5 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 3 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, and 0.3 parts of lubricant 4-7081.
[0090] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0091] SAG008:AX-71:UV326:1076=3:0.5:1:0.5;
[0092] 3) The PC resin was replaced with SABIC’s PC 101R-111 with an MI of 7 g / 10 min, and the PBT resin was replaced with Bluestar PBT1100 with a viscosity of 1.0 dL / g.
[0093] Example 8 A high performance anti-aging PC / PBT alloy material and its preparation method
[0094] The preparation method of Example 8 is the same as that of Example 1, except that the main material resin is replaced with another manufacturer's brand, and other conditions are the same.
[0095] 1) Weigh the following raw materials in parts by mass: 77.2 parts of PC resin, 10 parts of PBT resin, 5 parts of tetrabromobisphenol A polycarbonate, 0.4 parts of anti-drip synergist, 3 parts of compatible toughening agent BF-7M, 5 parts of compound anti-hydrolysis agent, and 0.3 parts of lubricant 4-7081.
[0096] 2) The compound anti-hydrolysis agent is composed of the following proportions:
[0097] SAG008:AX-71:UV326:1076=3:0.5:1:0.5;
[0098] 3) The PC resin brand was changed to LG 1201-10, medium viscosity, MI of 10g / 10min, and the PBT resin was changed to Kanghui KH-2085, viscosity of 0.825dL / g.
[0099] The flame retardant PC / PBT prepared in the above example is further tested for its performance.
[0100] Measure the mechanical properties of materials according to the following methods and standards:
[0101] The granulated resins of Examples 1 to 8 were placed in a blast drying oven at 100°C for 2-3 hours, and samples were prepared on an 80T injection molding machine. Two sets of samples were prepared, one for conventional testing and one for high temperature and high humidity aging testing. The performance difference before and after aging was compared to evaluate the hydrolysis resistance of the material. The test was conducted after cooling and placing for 24 hours. The test standard was the American standard and the test temperature was room temperature.
[0102] Tensile strength standard ASTM D638, specimen size is 57mm*127mm*3.2mm (effective size), tensile speed is 50mm / min;
[0103] Bending strength standard: ASTM D790, specimen size is 127mm*13mm*3.2mm, bending speed is 2mm / min;
[0104] Izod impact standard: ASTM D256, sample size is 64mm*12.7mm*3.2mm, notch residual width is 10.12mm; Melt index standard: ASTM D1238, test conditions are 260℃ / 2.16kg; Flame retardant performance is tested according to UL 94 standard;
[0105] The high temperature and high humidity aging test is carried out according to the method of Environmental testing-Part 2-67:Tests-Test Cy:Damp heat, steady state, accelerated test primarily intended for components in IEC60068-2-67, and performance comparison is carried out after 504 hours of testing.
[0106]
[0107] Table 1 Performance comparison of Examples 1-8 and commercially available flame-retardant PC / PBT alloy products (before 504 hours of high temperature and high humidity aging)
[0108]
[0109]
[0110] Table 2 Performance comparison of Examples 1-8 and commercially available flame-retardant PC / PBT alloy products (after 504 hours of high temperature and high humidity aging)
[0111] From the un-aging test data in Table 1, it can be seen that the high temperature and high humidity resistant PC / PBT alloy material prepared by the present invention has a notched impact strength of up to 508 J / m, a flame retardant grade of 1.5 mm V-0, a tensile strength of 56 MPa, a flexural strength of 72 MPa, and a flexural modulus of 2350 MPa, and has excellent mechanical properties and is suitable for flame retardant electronic and electrical housing products. In addition, before the aging test, the performance of the commercially available flame retardant PC / PBT alloy material was also compared, and the year-on-year performance was similar.
[0112] From the data in Table 2 after aging test, it can be seen that the performance retention rate of the high temperature and high humidity resistant PC / PBT alloy material prepared by the present invention is very good, the performance retention rate is above 70%, and the above performance can fully meet the application of electronic appliances, new energy batteries, and automobile industries; while the performance of the commercially available flame retardant PC / PBT alloy material is seriously attenuated, and important indicators such as the cantilever beam notch impact retention rate is less than 15%, the elongation retention is less than 15%, the tensile strength and bending retention rate are less than 60%, and the fireproof dripping ignites the cotton, which is reduced to V2 level. The material is seriously degraded after aging.
[0113] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high-performance anti-aging PC / PBT alloy material, characterized in that: The invention comprises the following raw materials in parts by weight:
2. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The PC resin has a medium-low viscosity and a melt index of 6-10g / 10min.
3. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The polybutylene terephthalate has a medium viscosity of 0.8-1.
2.
4. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The tetrabromobisphenol A polycarbonate has a bromine content of ≥52%.
5. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The anti-drip synergist is a coated PTFE anti-drip agent.
6. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The compatible toughening agent is EMA grafted GMA.
7. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The compound anti-hydrolysis agent is a compound hydrolyzing agent composed of an antioxidant, a benzotriazole ultraviolet absorber, an ester exchange inhibitor, and a styrene-acrylonitrile-glycidyl acrylate copolymer in a certain ratio.
8. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The lubricant is a silicone lubricant.
9. The high-performance anti-aging PC / PBT alloy material according to claim 1, characterized in that: The nucleating agent is an optimized mixture of organic components and inorganic components.
10. The high-performance anti-aging PC / PBT alloy material according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Weigh various raw materials according to the formula described in any one of claims 1 to 9; 2) Dry PC, tetrabromobisphenol A polycarbonate, and PBT resin at 120° C. for 3-4 hours, and then mix them evenly with all other raw materials; 3) The mixed raw materials are placed in the lower hopper of the extruder, and melt-extruded and granulated by a twin-screw extruder to obtain a high-performance anti-aging PC / PBT alloy material.
Citation Information
Patent Citations
PC / PBT alloy with flame retardance, low-temperature impact resistance and high weather resistance and preparation method of PC / PBT alloy
CN111117186A
Thermoplastic resin and molded article manufactured using the same
US20230383054A1
Cited By
Flame-retardant damp-heat-resistant PC / PBT alloy film and preparation method thereof
CN121379085A